Potensi Bisnis Fabrikasi Tulangan Pondasi Telapak - Slamet R.B. Prasetyo; Rohmahillah A.S.; Imam Junaidi; Tedy Pranadiarso (CV. Kalimasada Group, 2025)
The foundation reinforcement of footings is an important element in building construction that functions to transfer structural loads directly to the ground. This type of foundation is often used in buildings of less than 3 stories. The provision of this foundation can be carried out conventionally in the field using manual labor or by purchasing prefabricated products that have been processed off-site. This research aims to analyze the business potential of prefabricated footing reinforcement by comparing the time and cost efficiency between these two methods. The research methodology uses a case study approach on a residential construction project in the Jubung Area of Jember Regency by calculating work duration, labor requirements, and total material and labor costs for both scenarios. The analysis results show that off-site rebar fabrication generally offers significant time efficiency and potential cost savings, especially for medium to large-scale projects. Additionally, fabrication provides the advantage of more uniform work quality and minimizes the risk of errors in the field. Based on these findings, the foundation rebar fabrication business has good prospects in supporting the needs of modern construction projects that demand speed and cost efficiency.